Frecuencia de listeria monocytogenes y otras listerías en carne de pollo fresco y verduras frescas obtenidas en mercados y centros de abasto de Lima Metropolitana - Centurión P., Mabel S. (2006)
The objective of the present research was to determine the frequency of Lísteria monocytogenes in chicken meat and vegetable raw, obtained from various food market of Metropolitan Lima. Fifty samples of fresh chicken meat and 50 of fresh vegetables (asparagus, cabbage, celery, spinach and lettuce). The microbiologycal analysis was carried out according to methodology recormmended in the Bacteriological Analytical Manual of the FDA and NF ISO 11290-1. Listeria monocytogenes was isolates from chicken sample (2%) and from sample asparagus (2%).